ANALYSIS OF CHALLENGES AND POTENTIAL FOR VILLAGE ECONOMIC EQUITY THROUGH MSMES IN TULUNGAGUNG REGENCY - Niken Puspasari; Iradha Taqwa Sihidi; Salahudin Salahudin (DIA: Jurnal Administrasi Publik, 2022)
This study aims to analyze and describe various challenges and potentials in village economic equality. Based on the facts exposed, there arethe condition of the village is still lagging behind, so it is necessary for the economic empowerment of the MSME community to be proven to contribute to the Indonesian economy. The condition of the village is still lagging behind, so it is necessary to empower the community's economy. MSMEs have an important role in national development, namely employment, income distribution, rural economic development. However, in addition to the various obstacles that arise, there is a potential that creates opportunities to achieve economic equality in the village in accordance with the 17 goals of the SDGs. The research method applied in this research is the qualitative method of content analysis regarding the equitable distribution of the village economy. Data analysis using Nvivo 12 Plus. The results of the study reveal that the potential for village economic equality includes various aspects, namely the support of the central government, SDGs program, participation, technology and information support and natural resources with the highest rating, namely the support of the central government with a figure of 67.07%. The results show that they contribute to the formulation and development of science, especially government science related to the development of village SDGs, especially regarding the challenges and potential for equitable distribution of the village economy.